DEKOMPOSISI SERASAH DAUN AKASIA (ACACIA AURICULIFORMIS) DI KHDTK LITBANG KEHUTANAN OELSONBAI KOTA KUPANG) - Monika Ignasia Mali; Maria M. E. Purnama; Astin Elise Mau (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2021)
Decomposition defined as simple change of physical or chwmical caused by the activity of microorganisms ( soil bacteria, fungi, other land and animals or often called) mineralisasi also is destruction of organic material derived from animals and plants become simple organic of compounds that will be absorbed back into the ground. The measurement of decomposition litter the leaves do by putting a litter bag filled with litter Acacia leaves as many as 40 gr. Then, liiter bag will be placed at random as much as 30 litter bag around Acacia. The research is done for 3 months from February to April 2020. Litter are collected as many as 10 bags every month and the leaf dry weight was calculated at 75 °C for 24 hours. The measuements result will count with the formula a decline of weight and the rate of decomposition. The decomposition of litter based on the result of budget 8.175 % gr/ months or 98.1 x 10-6 tons/years. The decomposition of litter afected by many the suitability and makroorganisme microorganisms that have been flying to restore to soil nutrient. Then the decomposition of litter influenced by three main factors such as reverse engineered organisms, the quality of litter and the enviroment physic- chemichal.